The mechanism of wrinkling of cotton fabric in a front-loading washer: The effect of mechanical action. Issue 18 (September 2019) - Liu, Hong; Gong, Hugh; Xu, Pinghua; Ding, Xuemei; Wu, Xiongying
In order to understand the impact of mechanical action on the wrinkling of cotton fabrics in a drum washer, fabric movement was observed and a movement index system was developed to characterize the textile motion. Results showed that spinning speed and wash load were the major factors influencing the smoothness of cotton fabrics, with p values of 0.000 and 0.032, respectively. The analysis of fabric movement illustrated that when the wash load increased, the free motion region decreased and the ratio of passive motion region increased, resulting in severe wrinkling of cotton fabric. A regression model was developed to characterize the relationship between fabric movement and smoothness. These findings help the understanding of the mechanism of wrinkling during a drum washer washing.